The screening and characterisation of compounds for modulators of heat shock protein (Hsp90) in a breast cancer cell model,Screening and characterization of compounds for modulators of heat shock protein (Hsp90) in a breast cancer cell model - Moyo, Buhle (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
Breast cancer is a leading cause of cancer death in Africa. Hsp90 has been identified as a target for anti-cancer treatments as its inhibition results in the disruption and ubiquitin"“proteasome degradation of activated oncoproteins. Currently, there are no US Food and Drug Administration approved Hsp90 inhibitor drugs and existing Hsp90 inhibitors such as geldanamycin and novobiocin are hepatotoxic and display a low affinity for Hsp90, respectively. Therefore, there is a need for the development of Hsp90 inhibitors with improved inhibitory properties. In this study twelve natural compounds bearing a quinone nucleus were screened and characterised for the modulation of Hsp90. The compounds analysed formed three series; the sargaquinoic acid (SQA), naphthoquinone, and pyrroloiminoquinone alkaloid series. Certain compounds exhibited half maximal inhibitory concentrations of between 3.32 Î¼M and 12.4 Î¼M, while others showed no antiproliferative activity at concentrations of up to 500 Î¼M in the MDA-MB-231 breast adenocarcinoma cell line. Immunofluorescence and Western analyses indicated that the modulation of Hsp90 and partner proteins by SQA was more similar to that of novobiocin. Isothermal titration calorimetry analyses suggested that SQA interacted with Hsp90Î² with a low affinity, and saturation-transfer difference nuclear magnetic resonance confirmed that this interaction with Hsp90Î² occurred through the methyl moiety bound to 1, 4 benzoquinone of SQA. Pulldown assays indicated SQA disrupted the association between Hsp90 and Hop dose-dependently, more similarly to novobiocin. Immunofluorescence and Western analyses performed on naphthoquinone and pyrroloiminoquinone alkaloid compounds indicated modulation of Hsp90 and Hsp90 partner proteins by the compounds. Naphthoquinone compounds were prioritised for analysis for binding to Hsp90Î² over the pyrroloiminoquinone alkaloid compounds. Lapachol interacted with Hsp90Î² with a low affinity however; this interaction was thought to be too weak to disrupt the association of Hsp90 and Hop. The remaining naphthoquinone compounds showed no interaction with Hsp90Î², thus allowing the determination of a preliminary structure-activity relationship for these compounds. To the best of our knowledge, this is the first study to describe a systematic subcellular analysis of the effects of geldanamycin and novobiocin in comparison to sargaquinoic acid and compounds of the naphthoquinone and pyrroloquinoline scaffold on Hsp90 and its partner proteins.,Microsoftï¿½ Word 2010,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Heat shock proteins; Breast -- Cancer; Breast -- Cancer -- Chemotherapy; Breast -- Cancer -- Treatment; Cancer cells; Naphthoquinone; PQQ (Biochemistry)